PREVALENCE OF MENTAL RETARDATION AMONG CHILDREN IN MANGALORE - B., Bhagya; A., Ramakrishna (Journal of Health and Allied Sciences NU, 2013)
Objectives: This study determines the prevalence of mental retardation among school going children in Mangalore by sex, age, religion, and location. Distribution of severity of mental retardation and its relationship with age of diagnosis is reported.Materials and methods: The prevalence was obtained from the Inclusive Education Resource Centre reports of 2011. Sex, age, religion and living area were evaluated for each child. Parents of the mentally retarded children were interviewed to record the age of diagnosis. Intelligence Quotient was assessed using Binet Kamat Test, Seguin Form Board and Vineland Social Maturity Scale.Results: The prevalence of mental retardation was 561 of the total disabilities recorded.The prevalence of MR was higher among males than in females (p<0.001). No notable sex difference between rural and urban areas was seen. Prevalence was higher among Hindus and between 9 to 12 years of the age group. Most of them had mild MR (48.15%). Severe and Profound MR were diagnosed at a much earlier age group than in mild and moderate types.Conclusion: This study provides an insight to the school going children with mental retardation. Further research on study of causes for MR is needed for service planning.
Keywords: Mental retardation; Children; Prevalence; Intelligence Quotient; Mangalore